2018
DOI: 10.1016/j.ajoc.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Delayed-onset Candida parapsilosis cornea tunnel infection and endophthalmitis after cataract surgery: Histopathology and clinical course

Abstract: PurposeTo describe a patient with late post-operative endophthalmitis and clear cornea tunnel infection caused by Candida parapsilosis that was masquerading as chronic anterior uveitis.ObservationsA 62-year old woman with history of uncomplicated cataract surgery 7 months prior and chronic postoperative anterior uveitis, presented with an endothelial plaque, hypopyon, and infiltrates in the capsular bag and within the clear corneal tunnel. Anterior chamber cultures identified C. parapsilosis and pathology of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Fungal corneal tunnel infections after phacoemulsification surgery are uncommon. Palioura et al reported that there are 23 cases have been published in the literature [ 3 ]. Twelve eyes (52.2%) advanced to endophthalmitis with poor visual outcomes (visual acuity ≤ 6/120) in three patients, and loss of the eye occurred in four patients, three of which became phthisis bulbi and one underwent evisceration of the eye [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fungal corneal tunnel infections after phacoemulsification surgery are uncommon. Palioura et al reported that there are 23 cases have been published in the literature [ 3 ]. Twelve eyes (52.2%) advanced to endophthalmitis with poor visual outcomes (visual acuity ≤ 6/120) in three patients, and loss of the eye occurred in four patients, three of which became phthisis bulbi and one underwent evisceration of the eye [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Palioura et al reported that there are 23 cases have been published in the literature [ 3 ]. Twelve eyes (52.2%) advanced to endophthalmitis with poor visual outcomes (visual acuity ≤ 6/120) in three patients, and loss of the eye occurred in four patients, three of which became phthisis bulbi and one underwent evisceration of the eye [ 3 ]. The latency period between the date of cataract surgery and the presentation of the fungal tunnel infection varied from three days to 15 years with a median of one month [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Полостные хирургические вмешательства, в особенности при катаракте [42] и дренажной операции при глаукоме [41], также могут служить причиной развития грибкового эндофтальмита, однако процент их встречаемости крайне низкий и в основном связан с интраоперационном заносом бактериальных спор с инструментария, расходных материалов, рук персонала или кожных покровов пациента [38][39][40].…”
Section: рис 3 фундус-снимок глазного дна с признаками кандидозногоunclassified